Interrelationship of body mass index, dental caries, and oral health behaviour: Insights from Primary School in Surabaya, Indonesia - Sitalaksmi, Ratri Maya; Kartikasari, Nadia; Rahmania, Primanda Nur; Limantoro, Onny Eryanto; Wardati, Yora; Prajugo, Charlie Saputra; Yukuri, Annete Juwita; Putri, Hananah Oktalidial; Dhamayanti, Tiara Eva; Rudhanton, Riddo Adli; Gofur, Aisyah Rachmadani Putri (Faculty of Dental Medicine Universitas Airlangga, 2025)
Background: Dental caries is one of global health issues, with various factors such as Body Mass Index (BMI) and oral hygiene behaviours influencing its prevalence. Understanding the relationship between BMI and dental caries, as well as the oral hygiene practices, is essential for developing effective prevention strategies. Interventions on these factors arevital for mitigating the effects of dental caries on overall health. Purpose: This study aims to examine the correlation between dental caries and BMI in relation to oral and dental health behaviours. Methods: BMI and Decay, Missing, and Filled Teeth (DMF-T) data were collected from 5th-grade elementary school students, along with responses to an Oral andDental Health Care Questionnaire. Statistical analysis was conducted using the Kruskal-Wallis Test (p<0.05) and DwassSteel-Critchlow-Fligner (DSCF) (p<0.05). Results: No significant differences in caries indices were observed between genders (p>0.05). The majority of participants were classified as underweight, and this group demonstrated a lower caries index. A comparison of DMF-T scores across various BMI categories revealed a statistically significant difference (p<0.05). Furthermore, the post hoc test indicated a significant difference in BMI between the very low and low groups within the DMFT category (p<0.05). Conclusion: The findings suggest that good oral health practices is affecting the relationship between BMI and dental caries. Thus, the importance of promoting proper oral hygiene and early intervention to prevent dental caries and improve overall health outcomes. Preventive efforts should target at-risk groups, focusing onlifestyle and oral health education.